Media Literacy Enhancement of Chinese Youth: Case of Guangzhou University Students Regarding Information Fragmentation - Yu, Tian; Yossakrai, Kanokrat; Buranadechachai, Sukanya (Journal of Dhamma for Life, 2025)
The objectives of this research were (1) To study the current situation of the media literacy level of Guangzhou youths regarding information fragmentation; （2) To develop the media literacy training model for Guangzhou youths regarding information fragmentation; and （3）To propose the media literacy training guideline for Guangzhou youths regarding information fragmentation. The research was mixed methodology research. Population was university students aged 18-22 in the Guangzhou area, totalling 1.6 million. The sample size was determined by Taro Yamane (error 0.05), obtained by purposive sampling method, totaling 400 and using randomize table to selected 60 students for 30 students of control group and 30 students of experimental group. The 10 key informants were 1 college media professional teacher, 1 college ideological and political lecturer, 1 college student majoring in media, 1 non-media major college student, 2 parents of college students in Guangzhou, 2 media experts form Guangzhou, and 2 practice person who related to media literacy. The instruments used for data collection were questionnaire, in-depth interview, documents, and non-participatory observation. The statistics used for data analysis were frequency, percentage, mean, standard deviation, Paired T-test, and Independence T-test. The research findings revealed that; (1) Guangzhou is rich in higher education resources with important role in talent training and regional economic development. Moreover, it has faced the phenomenon of information fragmentation which lead the youth to misunderstanding, misdirection and information overload, (2) The media literacy training model for information fragmentation come from the curriculum which test from pre-test and post-test with significant level at (3) Researcher proposes information fragmentation of media literature training course comprises of 6 topics such as 1) exposure and use of social media, 2) safety and healthy use of media, 3) understanding and analysing media language and images, 4) identifying and responding to fake news, 5) information technology laws and media use, and 6) building and maintaining trust in online media.